2013
DOI: 10.3109/14017431.2013.865074
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction complicated by shock: outcome analysis based on initial electrocardiogram

Abstract: RBBB on admission ECG is associated with the highest risk of CS development, frequent left main coronary artery affection, and unsuccessful revascularization. It is also an independent predictor of one-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
6
7
0
3
Order By: Relevance
“…This finding is in accordance with earlier studies, as greater burden of coronary artery disease has been associated with an increased risk of CS in STEMI patients (Obling et al, 2017). An STDEP was associated with three-vessel disease, as previously depicted (Anderson et al, 2013;Holmes et al, 1999;Jacobs et al, 2000;Jakl et al, 2014), but the prevalence of the left main coronary artery disease was similar in the STE and STDEP groups, in contrast to earlier studies (Jacobs et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is in accordance with earlier studies, as greater burden of coronary artery disease has been associated with an increased risk of CS in STEMI patients (Obling et al, 2017). An STDEP was associated with three-vessel disease, as previously depicted (Anderson et al, 2013;Holmes et al, 1999;Jacobs et al, 2000;Jakl et al, 2014), but the prevalence of the left main coronary artery disease was similar in the STE and STDEP groups, in contrast to earlier studies (Jacobs et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…In the ACS subgroup analysis, the ST‐segment deviations were not associated with mortality, corresponding to some earlier studies (Jacobs et al, ; Jakl et al, ). However, the previous data is inconsistent; some contemporary studies have reported opposite results, where the prognosis of NSTEMI has been inferior to the prognosis of STEMI (Anderson et al, ; Jeger et al, ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Cardiogenic shock (CS) is the most severe complication of acute myocardial infarction (AMI) and is associated with high short-term mortality, despite advances in reperfusion therapy and modern intensive care 1,2 . In AMI, the incidence of CS increases from 5-8% up to 12-19% in the presence of a bundle branch block 1,[3][4][5] , especially with right bundle branch block (RBBB) 5,6 . Changes in the QRS duration and pattern in addition to ST segment deviations are regarded to reflect more severe ischemia and faster progression of irreversible myocardial necrosis than ST segment deviations alone 7,8 .…”
Section: Introductionmentioning
confidence: 99%